Peabody Museum : imagining the future of the Yale Peabody Museum of Natural History - Helfand, Jessica; Rosenthal, Jean (London : Yale School of Management, 2018)
In 2018, the Yale Peabody Museum of Natural History was about to go through a massive renovation. The physical makeover would add exhibition, classroom, and storage space, as well as updating the museum's infrastructure. Unfortunately, the museum would have to close to the public during for the two years of construction. But when it emerged, what would the museum be? What is the role for a university natural history museum in the 21st century?
Originally Published InHelfand, J., & Rosenthal, J. (2018). Peabody Museum: Imagining the future of the Yale Peabody Museum of Natural History. Yale SOM Case 18-010. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Peabody Museum of Natural History; Museum buildings -- Remodeling -- Connecticut -- New Haven; Public buildings -- Connecticut -- New Haven -- Design and construction; Public buildings -- Connecticut -- New Haven -- Maintenance and repair; Natural history museums -- Connecticut -- New Haven